Sociology of education : an A-to-Z guide - Ainsworth, James (Thousand Oaks, California : SAGE Reference, 2013)
The sociology of education is a rich interdisciplinary field that studies schools as their own social world as well as their place within the larger society. The field attracts contributions from education, sociology, human development, family studies, economics, politics and public policy. This guide introduces students to the social constructions of our educational systems and their many players, including students and their peers, teachers, parents, the broader community, politicians and policy makers. The roles of schools, the social processes governing schooling, and impacts on society are all critically explored.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Educational sociology -- Encyclopedias